Characteristics Of Financing Innovation Cluster - Akbarkhojaeva Nilufar Azimjanovna (Genius Publishing Group, 2023)
This article deals with the financing mechanisms of cluster activity, which is a new form of business management in industry today.
Keywords: clusters; investments; finance; financing mechanisms